Circulating Levels of Inflammatory Markers in Intrauterine Growth Restriction. (3rd June 2010) - Boutsikou, Theodora; Mastorakos, George; Kyriakakou, Marialena; Margeli, Alexandra; Hassiakos, Demetrios; Papassotiriou, Ioannis; Kanaka-Gantenbein, Christina; Malamitsi-Puchner, Ariadne
Abstract : We aimed to investigate possible alterations in circulating levels of the perinatal stress markers high sensitivity (hs)-CRP, PAI-1, and S100B—probably reflecting brain and adipose tissue inflammation—in intrauterine growth-restricted-(IUGR) and appropriate-for-gestational-age-(AGA) pregnancies, given that these groups differ in fat mass and metabolic mechanisms involving aseptic inflammation. Serum hs-CRP, PAI-1, and S100B levels were measured in 40 mothers, and their 20 AGA and 20 IUGR full-term fetuses and neonates on postnatal days 1 and 4. hs-CRP, PAI-1, and S100B levels did not differ at all time points between AGA and IUGR groups. We conclude that the lack of difference in hs-CRP, PAI-1 and S100B levels, between IUGR and AGA fetuses/neonates—despite the lower birth weight, reflecting reduced fat mass in the former—might indicate more intense adipose tissue and nervous system inflammation in IUGRs. However, implication of other inflammation-related mechanisms, common in the IUGR state (e.g. preeclampsia), cannot be excluded.